Genetic Background and Expression of the New qepA4 Gene Variant Recovered in Clinical TEM-1- and CMY-2-Producing Escherichia coli - Manageiro, Vera; Félix, David; Jones-Dias, Daniela; Sampaio, Daniel A.; Vieira, Luís; Sancho, Luísa; Ferreira, Eugénia; Caniça, Manuela (Frontiers in Microbiology, 2017)
A new QepA4 variant was detected in an O86:H28 ST156-fimH38 Escherichia coli, showing a multidrug-resistance phenotype. PAβN inhibition of qepA4-harbouring transconjugant resulted in increase of nalidixic acid accumulation. The qepA4 and catA1 genes were clustered in a 26.0-kp contig matching an IncF-type plasmid, and containing a Tn21-type transposon with multiple mobile genetic elements. This QepA variant is worrisome because these determinants might facilitate the selection of higher-level resistance mutants, playing a role in the development of resistance, and/or confer higher-level resistance to fluoroquinolones in association with chromosomal mutations.